Less and Non-invasive Hemodynamic Monitoring Techniques - Bernd Saugel (Frontiers Research Topics, 2018)
In the perioperative setting and in intensive care medicine, early and effective hemodynamic management including fluid therapy and administration of vasoactive drugs to maintain vital organ perfusion and oxygen delivery is mandatory. Understanding the different approaches in the management of critically ill patients during the resuscitation and further management is essential to initiate adequate context- and time-specific interventions. Optimization of hemodynamic variables to achieve a balance between organ oxygen delivery and consumption is a cornerstone. In general, cardiac output (i.e., the blood flow) is considered a major determinant of oxygen supply and thus its monitoring is regarded helpful. However, indicators of oxygen requirements are equally necessary to assess adequacy of oxygen supply. Currently, more and more less or even totally non-invasive monitoring systems have been developed and clinically introduced, but they require validation in particular clinical settings. Cardiac output monitors and surrogates of organ oxygenation only enable to adequately guide management, as patient's outcome is determined by acquisition and interpretation of accurate measurements, and finally, suitable management decisions. This Research Topic focuses on the currently available techniques, especially the less and non-invasive ones, in the field of hemodynamic monitoring in the perioperative setting and in critically ill patients while summarizing their advantages and limitations.